"Who Am I?": The Biblical Moses as a Metaphor for Teaching. (April 2015) - Gravett, Emily O.
Abstract This essay presents Moses, the protagonist of the biblical books of Exodus and Deuteronomy in the Hebrew Bible, as a playful but generative metaphor for current teaching practices and experiences in higher education, including my own. Among numerous similarities (such as the fact that Moses, other teachers, and I are all bound by context), the most humbling insights come from Moses's role as a mediator or intermediary. It is a role that we also inhabit – standing, as it were, between our students and the knowledge of our discipline – and that we might consider further, particularly in terms of our responsibilities.